Polymeric Hydrogels as Smart Biomaterials - Kalia, Susheel (Springer Series on Polymer and Composite Materials,, 2016)
This book is concerned with polymeric hydrogels, which are considered as one of the most promising types of new polymer-based materials. Each chapter in this book describes a selected class of polymeric hydrogels, such as superabsorbent hybrid nanohydrogels, conducting polymer hydrogels, polysaccharide-based or protein-based hydrogels, or gels based on synthetic polymers. In this way, the book also addresses some of the fascinating properties and applications of polymeric hydrogels: they are three-dimensional, hydrophilic, polymeric networks that can absorb, swell and retain large quantities of water or aqueous fluids. In combination with metal nanoparticles, nanofibrils or nanowhiskers, which may be embedded in the gels, they find widespread applications, ranging from agriculture, and waste water treatment, over electronics, to pharmaceutical and biomedical applications. Applications mentioned in this book include electro sensors, capacitors, electromechanical actuators, and even artificial muscles.